PEMBELAJARAN TEMATIK TANGGAP DARURAT DAN MITIGASI BENCANA ALAM MERAPI DI SEKOLAH DASAR (SD) RAWAN BENCANA - Tien Sotyaningrum, Afra; Hadisumarto, Rumsari (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2013)
The eruption of Mount Merapi has always impacted material and immaterial losses. For children, as a vulnerable group, it would affect the psychological trauma that will be taken until they are adults, and if it has left untreated will negatively impact the development of their spiritual and mental. Inspired by the experience of the disaster that struck Japan, which has a neat system ofdisaster mitigation, they perform disaster simulations in some of the most critical cities periodically. Each month the school conducts evacuation practices so that when disaster strikes, the children will know exactly what they should do. The method used in solving the problems is by Thematic Learning Emergency Response and Disaster Mitigation of Mount Merapi Disaster in Prone Elementary School. The method used is the method of playing and learning which comprises: a) developing a child's curiosity to explore questions related to the eruption of Mount Merapi; b) accompanying /guiding the children to do simple research to find answers to their questions; and c) assisting children to formulate the answers from their questions. The event ended with a simulation of P3K, the way to save themselves and others. This program has provided benefits for the children to prevent oriented and response oriented. The children will become prepared for disasters and know what to do when disaster strikes.Keywords: thematic learning, disaster mitigation, prevent oriented,response oriented